2010
DOI: 10.1158/0008-5472.can-09-4572
|View full text |Cite
|
Sign up to set email alerts
|

A NADPH Oxidase–Dependent Redox Signaling Pathway Mediates the Selective Radiosensitization Effect of Parthenolide in Prostate Cancer Cells

Abstract: Cancer cells are usually under higher oxidative stress compared with normal cells. We hypothesize that introducing additional reactive oxygen species (ROS) insults or suppressing antioxidant capacity may selectively enhance cancer cell killing by oxidative stress-generating agents through stress overload or stress sensitization, whereas normal cells may be able to maintain redox homeostasis under exogenous ROS by adaptive response. Here, we show that parthenolide, a sesquiterpene lactone, selectively exhibits … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
98
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(107 citation statements)
references
References 43 publications
8
98
0
1
Order By: Relevance
“…Other studies have shown that tumor cells have lower level of GSH (40) and GSTp (41) than normal cells. Higher levels of GSH and GSTp have been associated with drug resistance to chemotherapy.…”
Section: Discussionmentioning
confidence: 98%
“…Other studies have shown that tumor cells have lower level of GSH (40) and GSTp (41) than normal cells. Higher levels of GSH and GSTp have been associated with drug resistance to chemotherapy.…”
Section: Discussionmentioning
confidence: 98%
“…6,33 Inhibition of FOXO1/3 increases intracellular ROS through the regulation of antioxidant enzymes levels, such as MnSOD, sestrin, and catalase, and many experiments have shown that ROS have a critical role in determining life span and cellular senescence in mammalian cells. 5 In this study, ROS levels were elevated during IR-induced senescence, and the ROS scavenger NAC reverted IR-induced senescence phenotypes, including p53 activation, p21 induction, and SA-b-Gal activity.…”
Section: Discussionmentioning
confidence: 99%
“…However, the pathway of RIP3 mediated apoptosis has not been clearly elucidated. Furthermore, the influence of RIP3 on NF-κB, an inhibitor of apoptosis [22][23][24] , is controversial. In some studies, NF-κB appears to be induced by RIP3 overexpression [25,26] , but in other studies, RIP3 has no effect on its activation, but rather, acts by attenuating RIP1 and TNFR1-mediated NF-κB activation [27] .…”
Section: Discussionmentioning
confidence: 99%
“…PTL-induced apoptosis is also associated with increased ROS level in tumor cells because of the activation of NADPH oxidase and reduction of the cysteine group of the antioxidant, non-protein molecule glutathione [22,23] . ROS are ions or small molecules that include singlet oxygen molecules, free radicals and peroxides and are formed as byproducts of the normal cellular metabolism of oxygen [24] .…”
Section: Discussionmentioning
confidence: 99%